Response to "Restructuring the Organ Procurement and Transplantation Network contract to achieve policy coherence and infrastructure excellence". Issue 6 (31st December 2018) - Shepard, Brian; Dunn, Sue; Johnson, Maryl; Becker, Yolanda
Abstract : UNOS explains the importance of continuity and expertise in performing the OPTN contract. See Gentry and Segev's article onpage 1622 .